Dekonstruksi Ideologi di Balik Perubahan Tegalan Menjadi Hutan di Desa Riang Gede Tabanan Bali - Luh Putu Sri Ariyani; Tuty Mariyati; Nengah Bawa Atmadja (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
This critical ethnographic research aims to uncover the ideology behind the conversion of moors to forests and its implications for the sustainability of fields as an agricultural system. Data were collected through in-depth interviews, observation, and literature study. The results showed that the change of moor into the forest was due to the ideology adopted by farmers and the government's developmentalism and market ideology. This is complemented by binarism, which puts the moor in a negative connotation with rice fields. Binarism also applies to the younger generation, who views work as a farmer as unfavorable. This ideology is related to making the moor an agricultural system with no use, economic, sign, or symbolic value for farmers. The findings of this study can enrich the theory of ecological change due to the various ideologies. This research is expected to be the basis for various parties in making decisions to realize sustainable moor agriculture.